Evaluating How ‘Smart’ Brașov, Romania Can Be Virtually via a Mobile Application for Cultural Tourism - Briciu, Arabela; Briciu, Victor-Alexandru; Kavoura, Androniki (Sustainability, 2020)
Global urbanization brings the urge to identify the most intelligent methods to cope with the challenges arising in the modern society. Sustainable and smart cities are the new target for urban development; their representatives are being forced to identify and develop new strategies to increase their city’s performance and ensure that it endures over time. Information and Communication Technology (ICT) contributes to this purpose. Brașov is one of the cities in Romania for which the process of modernization started years ago, and it is currently developing as a smart city. This paper focuses on the development of the city in terms of cultural tourism solutions by presenting a case study on the use of virtual reality with a mobile application and its evaluation on cultural heritage sites. The original contribution of the paper is to describe and analyze the quality of the mobile application by using a proposed analysis grid to identify the main elements of this app. The main findings suggest that the application may bring authenticity of experience through the lens of heritage preservation for further user engagement and participation in real-time, while suggestions are made for future enhancement. Implications are discussed for a) destination managers, b) for developers to improve the general quality of the mobile application in terms of design and features and to implement changes in the near future, and c) for visitors who engage in real-time and co-create experiences.